Theoretical assessment of the effectiveness of the algorithm - Janys Арай; Nadyrova Фатима; Nurtazina Жанар (Рroblems of engineering and professional education, 2023)
The article contains a description of the algorithm for obtaining expressions developed by the author to analytically write the root of a system of linear algebraic equations. The reduced time of solving the system of equations when using this algorithm with fully filled matrices is theoretically justified. The speed of obtaining solutions is increased when using the algorithm based on sparse systems of equations, and at the same time, it is shown that the cost of RAM is reduced.